Phosphorylation-guarded light-harvesting complex II contributes to broad-spectrum blast resistance in rice - Liu, Muxing; Zhang, Suobing; Hu, Jiexiong; Sun, Wenxian; Padilla, Jonas; He, Yanglan; Li, Ying; Yin, Ziyi; Liu, Xinyu; Wang, Wenhao; Shen, Danyu; Li, Dayong; et al. (National Academy of Sciences, 2019)
Environmental conditions strongly influence pathogen–host plant interactions. Rice blast erupts in overcast and rainy conditions, due not only to favorable environmental conditions but also to insufficient light, which reduces host resistance. Due to the importance of breeding of blast-resistant rice varieties, elucidation of light-regulated rice immunity is an important research goal. We revealed that light induces protein phosphorylation of a harvesting complex II protein, LHCB5, upon infection by the rice blast fungus Magnaporthe oryzae . Resistance governed by LHCB5 phosphorylation cosegregates with the progenies harboring the desirable haplotype promoter. This establishes the genetic basis of LHCB5-regulated resistance mediated by phosphorylation. Our study highlights a mechanism for light-dependent rice blast resistance that promises future breeding of blast-resistant rice varieties.